Thermodynamic analysis of a pyroprocessing unit of a cement plant: a case study. (15th October 2012) - Atmaca, Adem; Kanoglu, Mehmet; Gadalla, Mohamed
The cement industry is one of the most intensive energy and cost industries in the world that consumes about 3800 MJ per tonne of cement produced. To achieve an effective energy management scheme, energy and exergy analyses were employed on the pyroprocessing unit of Gaziantep Cement Plant in Turkey. Energy and exergy efficiencies are determined to be 52.2% and 35.9%, respectively. Application of insulation on the unit reduced rate of heat loss from 22.7 MW to 17.3 MW. This in turn increases both the energy and the exergy efficiency values to 63.6% and 47.3%, respectively. The effect of weather conditions on the efficiency values is studied. It is estimated that 1056.7 kW of electricity can be generated by using the waste heat from the unit. The application of waste heat recovery steam generator prevents the emission of 5183 tons of CO2 to the atmosphere, representing a reduction of 8.2%.